In Silico Investigation of Betalaine Compounds from Hylocereus polyrhizus Peel as Antiplasmodial Agents - Eva Meilinda Puspita Sari; Shavinatus Zachro; Arsheila Suryawijayanti; Eka Yunita Wulandari (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Malaria is a parasite illness that continues to pose a global health challenge, largely because of the rise of medication resistance. Researchers are concentrating on discovering novel medicines that specifically target critical parasite proteins to address this issue. The peels of Hylocereus polyrhizus (dragon fruit) contain betalains which exhibit antiplasmodial activity. This research examines the efficacy of six betalaines derived from H. polyrhizus peels in inhibiting specific Plasmodium falciparum proteins through in silico techniques. Methods: The protein structures were acquired from the Protein Data Bank (PDB) and processed by eliminating non-protein molecules. The 3D structures of the betalaine ligands were obtained from PubChem and optimized with Avogadro 1.2.0. Using the Pyrx 0.8 system with Autodock Vina, the ligands were docked to the proteins. The research assessed ADMET characteristics of the ligands utilizing the SwissADME and ProTox-II platforms, respectively. Results: The molecular docking data indicate that Phyllocactin had the highest binding affinity of -10.7 kcal/mol to PfPNP. Hylocerenin had the highest binding affinity to PfDHFR-TS at -9.4 kcal/mol. The investigation of amino acid interactions indicated that Hylocerenin engages with essential residues, specifically Lys27 and Lys28, in PfDHFR-TS. Regarding ADMET characteristics, all six betalaines exhibited minimal gastrointestinal absorption and lacked permeability across the blood-brain barrier. Moreover, Hylocerenin was anticipated to be non-immunotoxic, presenting a notable benefit over other substances such as Betacyanin and Phyllocactin, which were forecasted to have immunotoxic effects. Conclusions: Hylocerenin and Phyllocactin are the most promising antiplasmodial possibilities among the examined betalaine compounds. Hylocerenin is a primary candidate for the inhibition of PfDHFR-TS, whereas Phyllocactin is a prominent candidate for the inhibition of PfPNP. The results indicate that betalaine compounds derived from H. polyrhizus peels merit more research as a novel category of antimalarial medicines